A new species and a key to species of the genus Coptotettix Bolivar, 1887 from India (Orthoptera: Tetrigoidea, Tetrigidae) - Gupta, Sunil Kumar; Chandra, Kailash (Zootaxa, 2017)
A new species of genus Coptotettix korbensis sp. nov. is described from Korba, Chhattisgarh, India. A key to known species of the genus Coptotettix from the Indian subcontinent is provided. The genus Coptotettix is the most diverse genus of Tetrigidae erected by Bolivar, 1887. This genus includes 79 species and subspecies from globally (Eades, et al., 2016), of which, 12 species are reported from India (Shishodia et al., 2010) i.e. Coptotettix annandalei Hancock, 1915 from West Bengal, Darjeeling, Singla; C. conspersus Hancock, 1915 from West Bengal, Siliguri; C. fossulatus Bolivar,1887 from Sri Lanka; C. indicus Hancock, 1912 from Bihar: Chapra; C. latifrons Brunner von Wattenwyl, 1893 from Myanmar, Palon (Pegu); C. lohitensis Shishodia, 1991 from Arunachal Pradesh: Lohit; C. manipurensis Shishodia, 1991 from Manipur: New Churachandpur; C. retractus Hancock, 1915 from Bihar: Pusa; C. hancocki Kirby, 1910 new name for Loxilobus rugosus Hancock, 1904 from Sri Lanka: Pundaluoya; C. testaceous Bolivar from Sri Lanka; C. tricarinatus Shishodia, 1991 from West Bengal: Darjeeling; C. tuberculatus Bolivar, 1887 from Malesia: Borneo. (Here only type locality provided)